A meta-analysis of the placebo response in antimuscarinic drug trials for overactive bladder - Creanga Dana; Malhotra Bimal; Lee Soyon; Carlsson Martin; Glue Paul (BMC Medical Research Methodology, 2009)
Abstract Background The purpose of this analysis was to characterize the placebo response in antimuscarinic drug trials for OAB, based on changes in commonly-used efficacy endpoints. Methods Placebo arm data for incontinence episodes, micturitions, voided volume and study characteristics were extracted from randomized placebo controlled antimuscarinic drug trials in OAB, from studies identified in a prior meta-analysis, and from a systematic review of more recently published studies. Relationships between variables were examined using linear regression, and changes in endpoints were analyzed by a meta-analysis approach. The effect of placebo arm size and magnitude of placebo response on probability of successful study outcome was analyzed using an ANOVA model. Results Changes in the placebo arms for all 3 endpoints were substantial and statistically significant, and highly heterogeneous. There were significant associations between baseline and change scores for some but not all of the endpoints. More recent studies tended to have more subjects than earlier studies, and there were positive associations between probability of achieving statistically significant results and size of the placebo arm. The magnitude of changes in placebo arms did not appear to influence the likelihood of the study to be statistically significant. Conclusion This analysis confirms earlier observation that the placebo response in OAB trials is substantial and highly heterogeneous. There are multiple potential reasons for this; however, these could not be explored in this analysis of study-level data. Two approaches may be used in clinical trials to manage high placebo effect: recruitment of 1) greater numbers of patients and/or 2) more severely affected patients; however, only the former approach is associated with increased probability of successful study outcome.